2022
DOI: 10.1038/s41528-022-00209-0
|View full text |Cite
|
Sign up to set email alerts
|

Strenuous exercise-tolerance stretchable dry electrodes for continuous multi-channel electrophysiological monitoring

Abstract: Electrophysiological monitoring under strenuous exercise by using stretchable dry electrodes is vital for healthcare monitoring, prosthetic control, human−machine interfaces and other biomedical applications. However, the existing dry electrodes are not applicable to the strenuous exercise situation that always involves both fast moving and profuse sweating. Herein, we present a nano-thick porous stretchable dry electrode system with high stretchability and water permeability. The system attaches conformably t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…As shown in Figure 9A, Xie et al reported multichannel electrophysiological monitoring of skin in real time 246 . The porous nanothick stretchable electrode was fabricated using the Marangoni effect and attached to the forearm and calves to collect EEG and EMG signals.…”
Section: Representative Examples Of Bioelectronic Systemsmentioning
confidence: 99%
“…As shown in Figure 9A, Xie et al reported multichannel electrophysiological monitoring of skin in real time 246 . The porous nanothick stretchable electrode was fabricated using the Marangoni effect and attached to the forearm and calves to collect EEG and EMG signals.…”
Section: Representative Examples Of Bioelectronic Systemsmentioning
confidence: 99%
“…Furthermore, human skin is fully covered with keratin with amino groups. 36 Besides the intermolecular attraction between the electrode and the epidermis, 34 covalent bonding can be established between the AAP/SEBS film and human skin, because of the chemical reaction releasing the succinimide (Figure 1B). Because of the amphiphilicity, AAP can act as a stabilizer at the interface between the organic solution and the water droplet to stabilize the porous morphology.…”
Section: Synthesis Of Adhesive and Amphophilic Polymer (Aap)mentioning
confidence: 99%
“…18 By liquid surface evaporation method, ultrathin styrene ethylene butylene styrene (SEBS) copolymer film electrodes with random pores are prepared with pore size in the range of 50−110 μm but wall thicknesses much thicker than 100 μm. 34 Even though porous films or fabrics are investigated for EP monitoring, a wall thickness of <10 μm has not been developed. To the best of our knowledge, there are few research on this unique type of stretchable and porous epidermal electrodes.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lots of interest is devoted to the fabrication of stretchable electrodes. [12][13][14][15][16] These electrodes need to possess matched modulus to adapt to the uneven surface of human skin/tissue. In addition to the mechanical properties, excellent conductivity, adhesion to skin, and biocompatibility are necessary.…”
mentioning
confidence: 99%